The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.19026/rjaset.6.3755
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Efficiency of Crimped Profile of Polypropylene Fibres on the Cementitious Matrix

Abstract: Fibre reinforcement in concrete is an effective solution for improving tensile properties of concrete. Different types of fibres such as steel, polypropylene, glass and polyester were commonly used in concrete. In the present study, the effect of adding crimped polypropylene fibres on the improvement in the compressive properties of hardened concrete was studied. Crimped polypropylene fibres with different levels of reinforcements index was investigated systematically with designed concrete mixtures consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Based on the calculations of cost effectiveness, INR 60/-is predicted to save 20% of costs. This is useful because India is a large country with a dense rural/urban road transport network where paver blocks can find potential applications [48,49]. Shrivastava and Bajaj [15] studied high-volume fly ash concrete of M20, M50 and M70 grades and replaced the OPC with 35%, 50% and 70% fly ash; they reported that the maximum flexural strength was attained at the 35% replacement level and saved 12% of the cost.…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…Based on the calculations of cost effectiveness, INR 60/-is predicted to save 20% of costs. This is useful because India is a large country with a dense rural/urban road transport network where paver blocks can find potential applications [48,49]. Shrivastava and Bajaj [15] studied high-volume fly ash concrete of M20, M50 and M70 grades and replaced the OPC with 35%, 50% and 70% fly ash; they reported that the maximum flexural strength was attained at the 35% replacement level and saved 12% of the cost.…”
Section: Cost Effectivenessmentioning
confidence: 99%
“…This method includes chemical etching, flame treatment, corona discharge or microwave radiation [44]. The significant improvement of adhesive capacity is obtained by the deformation of the fibres by crimping or twisting [45,46]. Other interesting option is application of fibrillated fibres with the net-like structure obtained from the polypropylene types [47][48][49].…”
Section: Introductionmentioning
confidence: 99%